If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2h + 9 = 3h Reorder the terms: 9 + 2h = 3h Solving 9 + 2h = 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 9 + 2h + -3h = 3h + -3h Combine like terms: 2h + -3h = -1h 9 + -1h = 3h + -3h Combine like terms: 3h + -3h = 0 9 + -1h = 0 Add '-9' to each side of the equation. 9 + -9 + -1h = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1h = 0 + -9 -1h = 0 + -9 Combine like terms: 0 + -9 = -9 -1h = -9 Divide each side by '-1'. h = 9 Simplifying h = 9
| (-2x+92)=(x+8) | | -5+4k=9k | | 4y-2(y+5)=0 | | 7v=-9+6v | | (4x+30)=(-2x+54) | | a-3=45 | | 10+4w=6w | | -5x+8x-4x=0 | | 9+9y=8y | | -5x+8x=0 | | -5p=-8+3p | | -[7x-(3x+4)]=-5-[4(2x-4)-2x] | | -21/-2 | | -3x+6x-7x=o | | y=7-(1/2)x | | 8/9*6/9 | | b=-21+-2d | | y^2-5x^2+50x+6y=141 | | -7x+5=-4x+27 | | SA=2(LW+lh+wh)forw | | Z+19=90 | | x-3t=yt | | 12h=9h | | -8x-6=50+3x | | 6t=-2 | | -8x-6=50 | | 2x-5=343 | | 6-3t=9t | | 5t=-2 | | 13x-(x+7)=12x-13 | | a(b)=30+b | | 4ab/2a |